The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1242/bio.037101
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamics of scaRNA2 and scaRNA9 in response to stress correlates with disrupted nuclear organization

Abstract: Small Cajal body-specific RNAs (scaRNAs) are part of small Cajal body-specific ribonucleoproteins (scaRNPs) that modify small nuclear RNA (snRNA) in Cajal bodies (CBs). Several scaRNAs (scaRNA 2, 9 and 17) have been found to generate smaller, nucleolus-enriched fragments. We hypothesize that the fragments derived from scaRNA 2, 9 and 17 form regulatory RNPs that influence the level of modifications within rRNA by altering small nucleolar RNP (snoRNP) activity. Here we show that external factors such as DNA dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Our previously published data ( Logan et al , 2018 ), and that shown in Figure 3 , support a role for Drosha and SYNCRIP in the processing of primary-scaRNA. To directly show that the Drosha/DGCR8 complex can process scaRNAs, we conducted in vitro processing assays using two different in vitro transcribed scaRNA9 transcripts.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Our previously published data ( Logan et al , 2018 ), and that shown in Figure 3 , support a role for Drosha and SYNCRIP in the processing of primary-scaRNA. To directly show that the Drosha/DGCR8 complex can process scaRNAs, we conducted in vitro processing assays using two different in vitro transcribed scaRNA9 transcripts.…”
Section: Resultssupporting
confidence: 79%
“…In contrast, WRAP53 knockdown does not result in a significant change in the amount of the mgU2-30 fragment derived from ectopically expressed primary-scaRNA9. These findings demonstrate that CB proteins differentially impact the processing of a specific primary-scaRNA, and SYNCRIP, which is part of the miRNA biogenesis machinery, contributes toward scaRNA fragment generation as does Drosha ( Logan et al , 2018 ).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Transcripts with a 12 h circadian period showed an enrichment for transcriptional activity, and for PI3K regulatory activity. Additionally, transcripts with differential rhythmicity were involved in RNA processing [35][36][37] and transcriptional regulation [38][39][40] , as well as PI3K/AKT signaling 41 . These findings corroborate results from rodent studies showing that fasted circadian sampling regulates skeletal and cardiac muscle anabolic signaling 27 .…”
Section: Discussionmentioning
confidence: 99%